Wagner–Meerwein-Type Rearrangements of Germapolysilanes - A Stable Ion Study - Albers, Lena (Organometallics, 2015)
[Image: see text] The rearrangement of tris(trimethylsilyl)silyltrimethylgermane 1 to give tetrakis(trimethylsilyl)germane 2 was investigated as a typical example for Lewis acid catalyzed Wagner–Meerwein-type rearrangements of polysilanes and polygermasilanes. Direct (29)Si NMR spectroscopic evidence is provided for several cationic intermediates during the reaction. The identity of these species was verified by independent synthesis and NMR characterization, and their transformation was followed by NMR spectroscopy.